2007
DOI: 10.1203/pdr.0b013e31802d8a4a
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal Ceroid Lipofuscinosis: A Common Pathway?

Abstract: ABSTRACT:The neuronal ceroid lipofuscinoses are pediatric neurodegenerative diseases with common clinical features. Of the nine clinical variants (CLN1-CLN9), six have been genetically identified. Most variants manifest cell death and dysregulated sphingolipid metabolism, suggesting the proteins defective in these disorders may interact along one pathway. NCL patientderived cell lines exhibit cell growth and apoptotic defects that reverse following transfection with the wild-type gene. The membrane-bound prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
38
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 60 publications
(42 citation statements)
references
References 20 publications
4
38
0
Order By: Relevance
“…Specifically, we used fibroblasts derived from a patient with LINCL, a disease caused by deficiency of tripeptidyl peptidase (TPP1) activity. Previous studies showed that cells derived from patients with LINCL or other NCLs have an increased tendency to undergo apoptosis (42). Thus, apoptosis-sensitive LINCL fibroblasts were selected for this study to investigate whether HP␤CD treatment affects autophagic clearance of ceroid lipofuscin and whether HP␤CD-induced modulation of autophagy also activates cell death mechanisms (see below).…”
Section: Hp␤cd Treatment Results In Clearance Ofmentioning
confidence: 99%
See 2 more Smart Citations
“…Specifically, we used fibroblasts derived from a patient with LINCL, a disease caused by deficiency of tripeptidyl peptidase (TPP1) activity. Previous studies showed that cells derived from patients with LINCL or other NCLs have an increased tendency to undergo apoptosis (42). Thus, apoptosis-sensitive LINCL fibroblasts were selected for this study to investigate whether HP␤CD treatment affects autophagic clearance of ceroid lipofuscin and whether HP␤CD-induced modulation of autophagy also activates cell death mechanisms (see below).…”
Section: Hp␤cd Treatment Results In Clearance Ofmentioning
confidence: 99%
“…To investigate whether administration of HP␤CD increases apoptosis under the conditions used in this study, we used LINCL fibroblasts, which present higher propensity to undergo apoptosis compared with wild type fibroblast (42). We monitored induction of early and late apoptosis by measuring membrane rearrangement, characteristic of early apoptosis (annexin V binding), and membrane fragmentation, characteristic of late apoptosis (propidium iodide binding), using the Cyto-GLO TM annexin V-FITC apoptosis detection kit as previously described (47).…”
Section: Hp␤cd Treatment Results In Activation Of Autophagy With-mentioning
confidence: 99%
See 1 more Smart Citation
“…There is growing experimental evidence relating the function of different NCL genes and pointing to possible shared biochemical pathways (Vesa et al, 2002;Siintola et al, 2006). It is tempting to speculate that the MFSD8/CLN7 gene product might act as an additional member in a common biochemical cascade, with protein dysfunction leading to neurodegeneration (Holopainen et al, 2000;Persaud-Sawin et al 2007). Further knowledge of these interactions will be important for development of therapeutic strategies (Mole et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The work uncovers a novel mechanism for neurodegeneration. NCL complementation groups regarding growth/ apoptosis, coimmunoprecipitation of NCL proteins and colocalization to subcellular compartments are described (38). Binding of CLN1/CLN2/CLN6/CLN8p to sulfatide/GalCer/LPA/ ceramide, and raft sphingolipid content/morphology from cells deficient in these proteins suggest lipid-binding/trafficking defects and raft sphingolipid content/morphology are common themes for NCL.…”
Section: Discussionmentioning
confidence: 99%